Determinants of Online Local Budget Transparency in Croatia and Slovenia - Katarina Ott; Mihaela Bronić; Branko Stanić; Maja Klun; Jože Benčina (Central European Public Administration Review)
As a part of the public governance, transparency started to come forward during the New Public Management reforms, mostly for the evaluation of public sector efficiency. This article focuses on online local budget transparency (OLBT) in two neighbouring countries – Croatia and Slovenia. The article is pioneering in a comparative study of the determinants of budget transparency in the Central and Eastern European (CEE) countries, based on a unique database and measure of transparency. The article tests the determinants of OLBT that reflect the accountability of local authorities and a cornerstone for public participation in the budget process. The following methodology was applied: using a data set of 768 Slovenian and Croatian local governments over the 2015–2017 period and testing it against several financial and socio-economic variables, and a random effects panel logistic regression, separately for Croatia, Slovenia, and a pooled sample. The results indicate that greater size of the population, higher administrative capacity and lower unemployment rate in individual local governments significantly contribute to higher levels of OLBT. This study demonstrates the possibility of developing a standardised measure of local budget transparency and using it to investigate the reasons for different levels of transparency in the two – and potentially other – CEE countries. The results of this and similar studies can serve as a basis for establishing cohesive local budget transparency policies for different countries and creating a combination of policy instruments to enhance transparency.